Cover Image, Volume 46, Issue 11. (12th July 2022) - Yin, Qing; Andò, Edward; Viggiani, Gioacchino; Sun, WaiChing
Abstract : The cover image is based on the Research Article Freezing‐induced stiffness and strength anisotropy in freezing clayey soil: Theory, numerical modeling, and experimental validation by Qing Yin et al., https://doi.org/10.1002/nag.3380 .